Analysis of the Effect of Copper Doping on the Optoelectronic Properties of Indium Oxide Thin Films and the Thermoelectric Properties of an In2O3/Pt Thermocouple - Yantao Liu; Tao Lin; Rong Huang; Jiahao Shi; Sui Chen (Crystals, 2024)
The detection and real-time monitoring of temperature parameters are important, and indium oxide-based thin film thermocouples can be integrated on the surface of heaters because they operate normally under harsh conditions and provide accurate online temperature monitoring. The higher stability and appropriate optical and electrical properties of In2O3 make it very suitable as an electrode material for thermocouple sensors. This work demonstrates that copper doping can alter the optical and electrical properties of In2O3 films and regulate the output performance of thermocouples. Copper-doped In2O3 thin films were prepared using the magnetron co-sputtering method. The doping concentration of Cu was controlled using direct current (DC) power. An In2O3/Pt thermocouple sensor was prepared, and the optoelectronic and thermocouple properties were adjusted by changing the copper doping content. The thickness valve of the thin film sample was 300 nm. The results of the X-ray diffraction suggested that the structure of the doped In2O3 thin films was cubic. The results of the energy-dispersive X-ray analysis revealed that Cu was doped into the In2O3 thin films. All deposited films were n-type semiconductor materials according to Hall effect testing. The 4.09 at% Cu-doped thin films possessed the highest resistivity (30.2 × 10−3 Ω·cm), a larger carrier concentration (3.72 × 1020 cm−3), and the lowest carrier mobility (0.56 cm2V−1s−1). The optical band gap decreased from 3.76 to 2.71 eV with an increase in the doping concentration, and the transmittance of the film significantly reduced. When the DC power was increased, the variation range of Seebeck coefficient for the In2O3/Pt thermocouple was 152.1–170.5 μV/°C, and the range of thermal output value was 91.4–102.4 mV.